Anatomija ledvic - Hribernik, Marija (Medicinski razgledi, 2005)
The kidney is a paired organ that is positioned on the lumbocostal triangle ofthe diaphragm and on the posterior abdominal wall muscles, outside of the peritoneal cavity and within a fibrous capsule and fatty tissue. It is composed of renal cortex containing the renal glomerules and the medulla that consists of renal pyramids. The peaks of these pyramids are surrounded by small renal calyxes which combine to form large renal calyxes and these finally constitute the renal pelvis. At the renal orifice, the pelvis merges with the urether without a clear demarcation line. Arterial blood is led to the kidney by the renal artery, which is a paired branch of the abdominal aorta and branches of perpendicularly, at the level of the second lumbar vertebra. The renal artery and its branches provide for the renal functional and nutritive blood flow.
Keywords: Kidney; Ledvica; Anatomy And Histology; Ledvična arterija; Ledvične vene; Renal Artery; Renal Veins; ledvice; anatomija; histologija